THE DEVELOPMENT OF THE MODERN SOCIETY ORDER MOVEMENT IN INDONESIA AND PAKISTAN - Ekawati Ekawati; Yani’ah Wardhani; Fatkhul Mubin (STAI ALHIKMAH Jakarta, 2022)
AbstractUrban Sufism is a phenomenon that occurs in almost all major cities in the world. In a metropolis environment that is increasingly strongly influenced by postmodern culture, the presence of classes of spirituality is both promising and worrying. On the one hand, the discourse of spirituality becomes the guardian of the